Assetization: A technoscientific or financial phenomenon? - Philipp Golka (Finance and Society, 2021)
Finance and financialization have dominated scholarship on capitalism and society for the past decade. Although scholars noted early on that the expansion of finance relies on the creation (and trade) of new financial assets, assets and assetization have been a blind spot as scholarship continued to focus on financial markets (Langley, 2020). This, however, is currently about to change as a number of landmark publications have been published in the past months that point toward growing momentum in the field of asset and assetization research. In this short essay, I review Kean Birch and Fabian Muniesa's edited collection, Assetization: Turning Things into Assets in Technoscientific Capitalism, which is of central importance to said momentum, and put it into dialogue with some of the other recent publications on this topic.
Keywords: 300; Assets; assetization; financialization; valuation studies; political economy